Significance of Lactobacillus fermentum on Antioxidative and Anti-Inflammatory Activities and Ultrafiltration Peptide Fractions as Potential Sources of Antioxidative Peptides from Fermented Camel Milk (Indian Breed). Issue 1 (2nd January 2023) - Patel, Dharmisthaben; Sakure, Amar; Lodha, Dikshita; Basaiawmoit, Bethsheba; Maurya, Ruchika; Das, Sujit; Bishnoi, Mahendra; Kondepudi, Kanthi Kiran; Hati, Subrota
Abstract: Objective: The present study aimed to assess the bio-functional analysis of camel milk viz. anti-oxidative, anti-inflammatory activities using potent Lactobacillus fermentum (KGL4) strain through fermentation and also to release the bioactive peptides during fermentation. Method: The antioxidant and proteolytic activities of the fermented camel milk were studied followed by SDS-PAGE analysis and 2 D PAGE. The separations of the bioactive peptides of water-soluble extract (WSE) of 3 and 10 kDa (Permeates & Retentates) were achieved by RP-HPLC. The purified bioactive peptides were identified and characterized using RPLC/MS and the effect of WSE of camel milk fermented with KGL4 on lipopolysaccharide (LPS)/endotoxin-induced inflammation in RAW 264.7 macrophages were also studied. Results: The maximal activity was observed in ABTS assay (64.03%), then in hydroxyl free radical scavenging assay, and minimal activity was observed in superoxide free radical assay (57.75%). ABTS assay was significantly (P < 0.05) higher than other assays. MTT assay was performed on WSE of camel milk fermented with KGL4 using treated macrophage cells with different concentrations and found the decreasing range of cell viability at 0.25 mg/mL treatment which was non-significant. 7.80 mg/ml peptide production was found after 48 h of fermentation using the OPA method. Further, WSE of fermented camel milk was separated and analyzed their protein profiles using SDS-PAGE and 2 D-PAGE techniques. Here, many new peptides were found in camel milk when fermented with KGL4 strain. Each protein sequence was characterized through bioinformatic tools, including SWISS-PROT & PIR protein databases. Novel bioactive anti-oxidative peptides were found by searching in the BIOPEP database. Conclusions: The present study suggests that the L. fermentum KGL4 strain could be explored to produce novel antioxidative peptides from fermented camel milk (Indian breed).